Redox regulation of SUMO enzymes is required for ATM activity and survival in oxidative stress - Stankovic-Valentin, Nicolas; Drzewicka, Katarzyna; König, Cornelia; Schiebel, Elmar; Melchior, Frauke (The EMBO journal, 2016)
Abstract To sense and defend against oxidative stress, cells depend on signal transduction cascades involving redox-sensitive proteins. We previously identified SUMO (small ubiquitin-related modifier) enzymes as downstream effectors of reactive oxygen species (ROS). Hydrogen peroxide transiently inactivates SUMO E1 and E2 enzymes by inducing a disulfide bond between their catalytic cysteines. How important their oxidation is in light of many other redox-regulated proteins has however been unclear. To selectively disrupt this redox switch, we identified a catalytically fully active SUMO E2 enzyme variant (Ubc9 D100A) with strongly reduced propensity to maintain a disulfide with the E1 enzyme in vitro and in cells. Replacement of Ubc9 by this variant impairs cell survival both under acute and mild chronic oxidative stresses. Intriguingly, Ubc9 D100A cells fail to maintain activity of the ATM?Chk2 DNA damage response pathway that is induced by hydrogen peroxide. In line with this, these cells are also more sensitive to the ROS-producing chemotherapeutic drugs etoposide/Vp16 and Ara-C. These findings reveal that SUMO E1~E2 oxidation is an essential redox switch in oxidative stress.